Myosin content of individual human muscle fibers isolated by laser capture microdissection - Stuart, Charles A. (Am J Physiol Cell Physiol, 2015)
Muscle fiber composition correlates with insulin resistance, and exercise training can increase slow-twitch (type I) fibers and, thereby, mitigate diabetes risk. Human skeletal muscle is made up of three distinct fiber types, but muscle contains many more isoforms of myosin heavy and light chains, which are coded by 15 and 11 different genes, respectively. Laser capture microdissection techniques allow assessment of mRNA and protein content in individual fibers. We found that specific human fiber types contain different mixtures of myosin heavy and light chains. Fast-twitch (type IIx) fibers consistently contained myosin heavy chains 1, 2, and 4 and myosin light chain 1. Type I fibers always contained myosin heavy chains 6 and 7 (MYH6 and MYH7) and myosin light chain 3 (MYL3), whereas MYH6, MYH7, and MYL3 were nearly absent from type IIx fibers. In contrast to cardiomyocytes, where MYH6 (also known as α-myosin heavy chain) is seen solely in fast-twitch cells, only slow-twitch fibers of skeletal muscle contained MYH6. Classical fast myosin heavy chains (MHC1, MHC2, and MHC4) were present in variable proportions in all fiber types, but significant MYH6 and MYH7 expression indicated slow-twitch phenotype, and the absence of these two isoforms determined a fast-twitch phenotype. The mixed myosin heavy and light chain content of type IIa fibers was consistent with its role as a transition between fast and slow phenotypes. These new observations suggest that the presence or absence of MYH6 and MYH7 proteins dictates the slow- or fast-twitch phenotype in skeletal muscle.